Composition of the Novel "Praghat" - Bishnu Neupane (Interdisciplinary Journal of Management and Social Sciences, 2025)
In the present article, an attempt has been made to identify the compositional structure of Narad Pokharel’s novel Pratighat as a text. In this article, structured in a qualitative format, facts have been collected from the work according to the purposeful sample selection method. Compositional structure has been made the theoretical basis in it. Structure and form are the compositional structure of a literary work. The structure of a novel includes plot, character, point of view, setting and essence. The subjects that help in the linguistic and stylistic construction of the novel include syntax, imagery, symbolism, comparison, satire, etc. In this article, the work of identifying the compositional structure of Pratighat has been done on the basis of these structure and form. This novel presents the ups and downs of Bimalraj, who grew up in the surroundings of the eastern hilly village of Simpani, and the events that occurred in his life, the characters who participated in those events, the environment there, their speech, customs and culture, and the ups and downs of their political consciousness. The ups and downs of the life of Bimalraj, the main character of the novel, are the subject of the story of this novel. Bimalraj is a representative character of those who worked day and night to change the discriminatory society and envision an ideal society. He has seen and experienced political distortions such as ideal and loyal political beliefs being disturbed, politics becoming a matter of money, having to drain money to get tickets, and having to spend money in elections. The structure of the novel has been prepared by narrating the life of a character who has ruined his own and his family’s future by getting involved in politics, who has not held any profitable position, and who has not been able to make any arrangements for his family. It has been concluded that the novel has a proper organization in structure and form, and is a novel presenting political themes.